'Saving Our Order': Becket and the Law. (May 2021) - Williams, Rowan
Abstract : The conflict between Henry II and Thomas Becket was often seen in the past as a collision between the first stirrings of real legal universalism (the same law for all) and claims to exemptions and immunities. Recent scholarship has seriously qualified this picture, recognising the degree to which Henry sought an unfettered authority for the Crown, overriding traditional patterns of obligation and mutuality. Becket's resistance to this was intelligible, but he was increasingly driven to oppose to it a controversial account of clerical immunity, in which the person of the cleric was sacrosanct and all punishment meted out to the cleric must be essentially reformatory in purpose. The origins of this are explored, and contemporary implications in regard to conscientious religious liberties and also to persisting high-risk cultures of clerical immunity are discussed.